Improved protein extraction and protein identification from archival formalin‐fixed paraffin‐embedded human aortas. Issue 3 (14th April 2013) - Fu, Zongming; Yan, Kun; Rosenberg, Avraham; Jin, Zhicheng; Crain, Barbara; Athas, Grace; Heide, Richard S. Vander; Howard, Timothy; Everett, Allen D.; Herrington, David; Van Eyk, Jennifer E.; Nirmalan, Niroshini; et al.
<x xml:space="preserve">Abstract</x> Purpose Evaluate combination of heat and elevated pressure to enhance protein extraction and quality of formalin‐fixed (FF), and FF paraffin‐embedded (FFPE) aorta for proteomics. Experiment design Proteins were extracted from fresh frozen aorta at room temperature (RT). FF and FFPE aortas (3 months and 15 years) were extracted at RT, heat alone, or a combination of heat and high pressure. Protein yields were compared, and digested peptides from the extracts were analyzed with MS. Results Combined heat and elevated pressure increased protein yield from human FF or FFPE aorta compared to matched tissues with heat alone (1.5‐fold) or at RT (8.3‐fold), resulting in more proteins identified and with more sequence coverage. The length of storage did adversely affect the quality of proteins from FF tissue. For long‐term storage, aorta was preserved better with FFPE than FF alone. Periostin and MGF‐E8 were demonstrated suitable for MRM assays from FFPE aorta. Conclusions and clinical relevance Combination of heat and high pressure is an effective method to extract proteins from FFPE aorta for downstream proteomics. This method opens the possibility for use of archival and often rare FFPE aortas and possibly other tissues available to proteomics for biomarker discovery and quantification.